Legal Protection of Land Tenure by Foreign Investors through Nominee Agreement in Bali, Indonesia - Nahak, Simon; Budiartha, I Nyoman Putu (International Journal of Criminology and Sociology, 2021)
This paper aims to describe legal protection as the provision of legal certainty to every citizen, individual or legal entity, to fight for and/or defend their rights and obligations by law enforcement officers and/or authorized officials in a certain place. More specifically, the analysis was conducted by using the socio-legal approach to examine the legal protection of land tenure by foreign investors through the nominee agreement in Bali, Indonesia. Moreover, the method was also done by using a normative approach through the analysis of legal matters in Indonesian laws. The legal basis is regulated in the basic constitutional provisions of the 1945 Constitution of the Republic of Indonesia, the Criminal Code, the Civil Code, the Basic Agrarian Law, the Environmental Act, Tourism Act, Investment Act, Government Regulation No. 41 of 1996 concerning ownership of residential houses or dwellings by foreigners domiciled in Indonesia. The results showed that there is no exception to foreign investors who contribute to the community also get legal protection. To carry out these investment activities requires land that is sometimes controlled by using nominee. The nominee is someone who acts for and on behalf of another party as the endorsee/guardian, agent/representative of the nominee/simulation/fake agreement. Sociological outlook showed that the sociological basis of Balinese society consists of a spiritual community that upholds local culture because many foreign citizens visit and reside because they want to take a vacation to visit the tourist area and find work in Bali, especially working in the field of tourism services and other fields of work that revive the community in Bali.